ANALISIS PENGELOLAAN ARSIP STATIS DEBITUR PADA DIVISI LOAN WORKOUT PT BANK CIMB NIAGA, Tbk. - Selly Filanda; Ennike Rahayu Lestari; Gustinawati Gustinawati; Retnowati WD Tuti (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2022)
Debtor static archive management research was conducted to find out the provisions or administrative guidelines related to the static credit document filing system in the Loan Workout Commercial Banking and Enterprise Banking Business (LWO COMBA and EBB) divisions at PT. Bank CIMB Niaga, Tbk. This research is interesting to do because there is a different management of static archives due to the reduction in workspace due to the Covid-19 outbreak. To achieve the research objectives, data from 3 (three) informants are needed who understand the management of static archives. Using qualitative methods with a case study approach. Research data sourced from observation with participation, unstructured interviews and documentation. Using the triangulation validity test and data analysis techniques using the Miles model from Huberman and Saldana (2014). The results of this study refer to the theory of archive management The Liang Gie (2009) which includes four indicators. The debtor static archive storage system only consists of three indicators, namely archive storage according to the alphabet of the debtor's name, the subject matter according to the classification of credit document storage rules and sorting the dates listed on the credit documents. Meanwhile, regional indicators are not included in the filing rules by PT Bank CIMB Niaga, Tbk. and the number indicator is done by numbering the orderner and the archive storage box